Antibodies to endothelial cells in Behçet's disease: cell-binding heterogeneity and association with clinical activity. Issue 4 (April 1994) - Cervera, R; Navarro, M; López-Soto, A; Cid, M C; Font, J; Esparza, J; Reverter, J C; Monteagudo, J; Ingelmo, M; Urbano-Márquez, A
Abstract : OBJECTIVES–To investigate the prevalence and characteristics of antibodies to endothelial cells (aEC) from large vessel and from microvasculature in a group of patients with Behçet's disease (BD) to determine the relationship of these antibodies with clinical and laboratory features of the disease. METHODS–Thirty patients with BD were prospectively and consecutively studied. The aEC were determined by enzyme-linked immunosorbent assay (ELISA) using endothelial cells derived from human umbilical vein (large vessel) as well as from retroperitoneal adipose tissue (microvasculature). RESULTS–Fifteen patients (50%) had aEC, either directed to large vessel [8(26%) patients] or microvascular [13(43%) patients] endothelial cells. The percentage of active patients was significantly higher in the aEC-positive group [12(80%) patients] compared with the aEC-negative group [5(33%) patients] (p < 0.05). CONCLUSIONS–Patients with BD have a high prevalence of aEC when microvascular endothelial cells are used in the assay. These antibodies seem to be a marker of disease activity in this condition, previously considered as negative for autoantibodies.